Relationship between CYP2B6*6 and cold pressor pain sensitivity in opioid dependent patients on methadone maintenance therapy (MMT). (1st August 2016) - Zahari, Zalina; Lee, Chee Siong; Ibrahim, Muslih Abdulkarim; Musa, Nurfadhlina; Mohd Yasin, Mohd Azhar; Lee, Yeong Yeh; Tan, Soo Choon; Mohamad, Nasir; Ismail, Rusli
Highlights: CYP2B6 polymorphisms contribute to variations in methadone pharmacokinetics. CYP2B6*6 carriers had shorter pain threshold than CYP2B6*6 non-carriers. Pain tolerance was also shorter in the CYP2B6*6 carriers. CYP2B6*6 influences pain sensitivity among patients on methadone maintenance therapy. Abstract: Background: CYP2B6 polymorphisms contribute to inter-individual variations in pharmacokinetics of methadone. Increased pain sensitivity is frequently reported by opioid dependent patients on methadone maintenance therapy (MMT). It is possible, therefore, that genetic polymorphisms in CYP2B6, which affects the metabolism of methadone, influence pain sensitivity among patients on MMT. This study investigated CYP2B6 polymorphisms and pain sensitivity in this group. Methods: The cold pressor pain responses of 148 opioid dependent patients receiving MMT were evaluated using the cold pressor test (CPT). DNA was extracted from whole blood and subjected to polymerase chain reaction (PCR)-genotyping. Results: Of the 148 subjects, 77 (52.0%) were carriers of CYP2B6*6 allele. CYP2B6*6 allele carriers had shorter cold pain threshold and pain tolerance times than non-carriers of CYP2B6*6 allele (21.05 s vs 33.69 s, p  = 0.036 and 27.15 s vs 44.51 s, p  = 0.020, respectively). Pain intensity scores of the CYP2B6*6 allele carriers was 67.55, whereas that of the CYP2B6*6 allele non-carriers was 64.86 ( p  = 0.352). Conclusion: Our study indicates that the CYP2B6*6 allele is associated with a lower pain threshold and lower pain tolerance among males with opioid dependence on MMT. The CYP2B6*6 allele may provide a mechanistic explanation for clinical observations of heightened pain sensitivity among opioid dependent patients receiving MMT.